2019
DOI: 10.1101/821280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stepwise endonuclease activity of a thermophilic Argonaute protein

Abstract: Thermophilic Argonaute proteins (Agos) can function as endonucleases via specific guide-target base-pairing cleavage for host defense. The ability to cleave target DNA sequences at any arbitrary sites endows them with reprogramed DNA capacity. Here, we identify that an Ago from the hyperthermophilic archaeon Pyrococcus furiosus (PfAgo) shows a stepwise endonuclease activity, which is demonstrated by the double strand DNA cleavage directed by a single guide DNA rather than canonical one pair of guide DNAs. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Here, we suggest the importance of these hot spots positions for gDNA design, which may contribute to conformational changes between the guide to WT or SNV target thus lead to the discrimination effect. In consistent with our previous results, the adjacent mismatches at 10–11 position of gDNA significantly affect cleavage activity of Pf Ago in a sequence-independent manner ( 39 ). Therefore, we establish the rule for gDNA design: a 16 nt gDNA with introduced single mismatch located at position adjunct with corresponding SNV site, to gain the continuous mismatches at 10–11 position for SNV target, and refer to single mismatch at position either 10 or 11 for WT target, to achieve the best discrimination.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we suggest the importance of these hot spots positions for gDNA design, which may contribute to conformational changes between the guide to WT or SNV target thus lead to the discrimination effect. In consistent with our previous results, the adjacent mismatches at 10–11 position of gDNA significantly affect cleavage activity of Pf Ago in a sequence-independent manner ( 39 ). Therefore, we establish the rule for gDNA design: a 16 nt gDNA with introduced single mismatch located at position adjunct with corresponding SNV site, to gain the continuous mismatches at 10–11 position for SNV target, and refer to single mismatch at position either 10 or 11 for WT target, to achieve the best discrimination.…”
Section: Resultssupporting
confidence: 92%
“…This result suggests that a single-nucleotide difference in the gDNA for the WT and SNV alleles was not sufficient to precisely differentiate the undesired allele for DNA cleavage under the evaluated conditions. The single nucleotide mismatch between the gDNA to target has been systematically evaluated in our previous study, and the result showed some positions of mismatch affected the cleavage activity but in dependence of target sequences ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An artificial restriction enzyme platform based on Pyrococcus furiosus Argonaute ( Pf Ago) was developed to recognize and cleave DNA sequences at virtually any arbitrary site ( Enghiad and Zhao, 2017 ). Furthermore, thermophilic pAgos have been recently used as programmable tools for specific target detection and rare single nucleotide variant enrichment in molecular diagnosis applications ( He et al, 2019 ; Xun et al, 2019 ; Liu et al, 2021a ; Song et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This device consists of 3D printed casing and internal structure with precise temperature control and fluorescence detection, whereas this assay combines RT-LAMP with an Argonaute protein from hyperthermophilic archaeon Pyrococcus furiosus (PfAgo) capable of precise recognition and cleavage of a target DNA at 95°C as directed by small 5′-phosphorylated single strand DNA (ssDNA) as guide DNA (gDNA) 10,11 . Due to the multi-turnover activity of PfAgo, its secondary cleavage mechanism can be harnessed for specific, sensitive, and multiplex nucleic acid detection 12,13 . For COVID-19 samples, although nasopharyngeal swab and nasal swab samples were recommended for detection of SARS-CoV-2, saliva samples are a more attractive alternative due to the ease, safety, and non-invasive nature of its collection 14,15 , and its relatively high viral load during the first week of infection 16 .…”
mentioning
confidence: 99%